2007
DOI: 10.1111/j.1532-950x.2007.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Biomechanical Comparison of Cervical Disk Arthroplasty, Ventral Slot Procedure, and Smooth Pins with Polymethylmethacrylate Fixation at Treated and Adjacent Canine Cervical Motion Units

Abstract: Cervical arthroplasty should be further investigated in vivo to determine if it is a viable alternative to the ventral slot or pin-PMMA procedures for surgical treatment of cervical diseases in dogs and in particular for treatment of disk-associated caudal cervical spondylomyelopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 50 publications
1
41
0
Order By: Relevance
“…[8][9][10]27,30 Because of the high rates of surgical failure and long-term recurrence, new methods are continually investigated for the treatment of disk-associated CSM in dogs. This type of prosthesis was used and tested in an earlier in vitro study 1 ; results of that study revealed that cervical vertebral column specimens from canine cadavers in which the prosthesis was implanted had biomechanical actions more similar to those of an intact vertebral column, compared with specimens in which ventral slot and pin-PMMA fixation procedures were performed. The goal of cervical arthroplasty is to preserve intervertebral mobility after neural decompression while providing distraction and stability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10]27,30 Because of the high rates of surgical failure and long-term recurrence, new methods are continually investigated for the treatment of disk-associated CSM in dogs. This type of prosthesis was used and tested in an earlier in vitro study 1 ; results of that study revealed that cervical vertebral column specimens from canine cadavers in which the prosthesis was implanted had biomechanical actions more similar to those of an intact vertebral column, compared with specimens in which ventral slot and pin-PMMA fixation procedures were performed. The goal of cervical arthroplasty is to preserve intervertebral mobility after neural decompression while providing distraction and stability.…”
Section: Discussionmentioning
confidence: 99%
“…The cervical prosthesis used was a titanium alloy version (Ti-6AI-4V-ELI) e of a prosthesis evaluated in an in vitro study 1 and consisted of 2 end plates, with a range of movement of 30° between plates (Figure 2). The cranial surface of the cranial end plate and the caudal surface of the caudal end plate were convex to avoid prosthesis migration and had concentric grooves to allow bone ingrowth into the prosthesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In accord with that, new compressive tion, ventral slot is much more time consuming, as it is a technically demanding technique. It is unclear if the defect generated leads to instability, as suggested by in vitro studies, because it is difficult to assess the compensative mechanisms in live animals (e.g., muscle contraction) (Lemarie et al, 2000;Agnello et al, 2010) or the expected secondary fibrosis at the treated site (Adamo et al, 2007).…”
Section: Conservative (Non-surgical) Treatmentmentioning
confidence: 99%
“…Due to the high incidence of domino lesions, it has been reported that motion preservation at the surgery site may reduce the rate of this common complication. According to Adamo et al (2007), ventral slot combined with an artificial disc prosthesis was better able to mimic the behavior of intact cadaver spines compared to ventral slot alone or the pin-polymethylmethacrylate technique. the initial and permanent distraction of the affected intervertebral disc space without the common complication of vertebral end plate failure-resorption and consequent loss of distraction (McKee et al, 1989;Rusbridge et al, 1998;McKee et al, 1999).…”
Section: Complicationsmentioning
confidence: 99%